2017
DOI: 10.3390/medicines4010016
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Cohort Study on the Ability of Acupuncture to Reduce Post-Stroke Depression

Abstract: Objective: Post-stroke depression (PSD) is common and has a negative impact on recovery. Although many stroke patients in Taiwan have used acupuncture as a supplementary treatment for reducing stroke comorbidities, little research has been done on the use of acupuncture to prevent PSD. Accordingly, our goal is to investigate whether using acupuncture after a stroke can reduce the risk of PSD. Method: This population-based cohort study examined medical claims data from a random sample of 1 million insured peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…[28] One study reported that patients with PSD who underwent higher frequency acupuncture treatments may have experienced greater improvement of depressive symptoms. [29] Because of the small number of studies, we cannot compare the effects of electroacupuncture, acupuncture combined with moxibustion, and traditional acupuncture. Moreover, the selection of acupoints in the included studies was not the same and, therefore, further research to optimize acupoint selection and improve the therapeutic schedule is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…[28] One study reported that patients with PSD who underwent higher frequency acupuncture treatments may have experienced greater improvement of depressive symptoms. [29] Because of the small number of studies, we cannot compare the effects of electroacupuncture, acupuncture combined with moxibustion, and traditional acupuncture. Moreover, the selection of acupoints in the included studies was not the same and, therefore, further research to optimize acupoint selection and improve the therapeutic schedule is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A few, however, claim no benefit came from the treatments. Studies in CAM for stroke recovery have highlighted the benefits of acupuncture, massage, exercises and herbal or vitamin supplements [64][65][66][67][68][69]. These studies argue that CAM aids with symptom relief increased mobility and improved mood in stroke survivors.…”
Section: External Mediatorsmentioning
confidence: 99%
“…Studies have suggested that acupuncture can reduce the incidence of PSD and relieve its symptoms. [10][11][12] Several existing meta-analyses [13][14][15] also indicate that acupuncture has a superior therapeutic effect to antidepressants on PSD. However, these studies only compared acupuncture versus antidepressants, while, in clinical practice, the use of acupuncture together with antidepressants is more prevalent.…”
Section: Introductionmentioning
confidence: 99%